Estratégias enunciativas em textos da campanha publicitária “pense ão” do jornal o Estado de S.Paulo. Uma análise semiótica - Clemente, Naiara Pedon Carvalho (2008)
This work analyses some texts of the advertising campaign “Pense ÃO” of the periodical “O Estado de S. Paulo”. The theoretical presuppositions were taken from French Semiotics. The campaign, elaborated by the Talent Agency, was propagated in the media printed during the year of 2006. The constituent texts of the corpus are analysed in its enunciative dimension, observing the relation between enunciator and enunciatee, and in its condition of syncretic texts. We observe the relation between the visual language and the verbal one, describing the topological, chromatic and eidetic dimensions in the visual plans, with the objective to apprehend the effects of sense that they produce in its relation with the verbal plan. We describe the construction of the process of signification of the texts and we analyse the enunciative strategies that are used by the enunciator to manipulate the enunciatee. These texts are also analysed in its figurative, narrative and passional dimensions. Key words: O Estado de S. Paulo, Campaign “Pense ÃO”, syncretism, enunciator, enunciatee